2015
DOI: 10.1002/2014ja020682
|View full text |Cite
|
Sign up to set email alerts
|

Postmidnight depletion of the high‐energy tail of the quiet plasmasphere

Abstract: The Van Allen Probes Helium Oxygen Proton Electron (HOPE) instrument measures the high‐energy tail of the thermal plasmasphere allowing study of topside ionosphere and inner magnetosphere coupling. We statistically analyze a 22 month period of HOPE data, looking at quiet times with a Kp index of less than 3. We investigate the high‐energy range of the plasmasphere, which consists of ions at energies between 1 and 10 eV and contains approximately 5% of total plasmaspheric density. Both the fluxes and partial pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 82 publications
1
25
0
Order By: Relevance
“…Figure (right column) shows the relative variability or the standard deviation ( σ D ) divided by the mean ( μ ). We have used fraction instead of percent to quantify the uncertainty and variability of the measurements to be consistent with our earlier studies on this subject [ Sarno‐Smith et al , ]. For 1.5 eV and 3.0 eV, the relative variability is higher in the postmidnight sector, especially at pitch angles near 0° and 180°.…”
Section: Methodssupporting
confidence: 69%
See 3 more Smart Citations
“…Figure (right column) shows the relative variability or the standard deviation ( σ D ) divided by the mean ( μ ). We have used fraction instead of percent to quantify the uncertainty and variability of the measurements to be consistent with our earlier studies on this subject [ Sarno‐Smith et al , ]. For 1.5 eV and 3.0 eV, the relative variability is higher in the postmidnight sector, especially at pitch angles near 0° and 180°.…”
Section: Methodssupporting
confidence: 69%
“…Outside the postmidnight sector, variability is higher at all MLTs compared to the 1.5 and 3.0 eV energy channels. Sarno‐Smith et al [] also found similar variability differences at different MLTs but showed in Figure 7 that although the postmidnight sector had higher relative variability, the bulk of the postmidnight sector 1–10 eV fluxes were still significantly below (greater than an order of magnitude) the 1–10 eV fluxes outside the postmidnight sector.…”
Section: Methodsmentioning
confidence: 61%
See 2 more Smart Citations
“…Using this Van Allen Probes-based model the estimated total plasmaspheric mass inside L = 5 is between 600 t ( Figure A1c) and 790 t ( Figure A1d). However, there is a very shallow postmidnight dip in T H + (or T He + ) that is not inconsistent with the postmidnight depletion in superthermal H + ions observed by Van Allen Probes (Sarno-Smith et al, 2015;, Sarno-Smith, Liemohn, Skoug, Santolik, et al,2016. Nonetheless, even in the lower-limit case the O + distribution contributes tens of metric tons, about 13% of the total plasmaspheric mass.…”
Section: Discussionmentioning
confidence: 65%